2016
DOI: 10.1002/mrd.22674
|View full text |Cite
|
Sign up to set email alerts
|

The role of mating in oviduct biology

Abstract: SUMMARYThe oviduct connects the ovary to the uterus, and is subject to changes that influence gamete transport, fertilization, and early embryo development. The ovarian steroids estradiol and progesterone are largely responsible for regulating oviduct function, although mating signals also affect the female reproductive tract, both indirectly, through sensory stimulation, and directly, through contact with seminal plasma or spermatozoa. The resulting alterations in gene and protein expression help establish a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 78 publications
(109 reference statements)
0
13
0
Order By: Relevance
“…None are obvious candidates contributing to known dog traits; rather, all play roles in basic cell biology. CACNG4, for instance, is a calcium channel regulator with many roles, among the most interesting is its involvement in the oxytocin signaling pathway, potentially suggesting a role in behavior [39]. Given the different personalities of the POOD and LAB breeds it would be interesting to investigate this finding in greater detail [39].…”
Section: Plos Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…None are obvious candidates contributing to known dog traits; rather, all play roles in basic cell biology. CACNG4, for instance, is a calcium channel regulator with many roles, among the most interesting is its involvement in the oxytocin signaling pathway, potentially suggesting a role in behavior [39]. Given the different personalities of the POOD and LAB breeds it would be interesting to investigate this finding in greater detail [39].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…CACNG4, for instance, is a calcium channel regulator with many roles, among the most interesting is its involvement in the oxytocin signaling pathway, potentially suggesting a role in behavior [39]. Given the different personalities of the POOD and LAB breeds it would be interesting to investigate this finding in greater detail [39]. TBC1D5 regulates endosomal trafficking [40], and MPDZ is related to eye and brain anomalies [41,42].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Recently, we demonstrated that SP can protect spermatozoa against the hostile uterine environment by preserving sperm motility and acrosome integrity after 3 h of incubation [ 21 ]. Indeed, SP can be found within the female genital tract up to 4 h after insemination [ 22 ], and the presence of SP has been observed in the oviduct in mice [ 23 ]. Another characteristic is that the SP contains proteins that bind to the sperm membrane creating a protective layer to avoid damage during their passage within the uterus, with these proteins being involved in different processes, such as sperm survival and the final stages of sperm maturation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned mating factors seem to change gene and protein expression post-coitus, consequently modulating uterine and oviductal functions [23]. Such modifications elicited in the reproductive tract help to create a suitable environment necessary for sperm storage [24], gamete transport, pre-implantation development, increased angiogenesis, and also changes in the immune system pattern [25,26], including the attainment of a status of tolerance to foreign proteins and cells. Although GC signaling is essential for the establishment and maintenance of fertility [1], the up-stream triggers causing the modifications of NR3C1-related genes after natural mating or insemination in the preovulatory phase are yet to be determined.…”
Section: Introductionmentioning
confidence: 99%